STABILITY ANALYSIS OF EMBANKMENT SLOPE USING BISHOP METHOD IN LUBE MODULE AREA PT. X - Satriawan, Satriawan; Alaydrus, Alfina Taurida; Minardi, Suhayat; Zulfatiha, Septhia Salwa (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2025)
The stability of embankment slopes in open-pit mining areas is a crucial factor in ensuring work safety and continuity of mine operations. This study aims to analyze the stability of embankment slopes in the Lube Module area of PT X using the simple Bishop method. The analysis was conducted by modeling the slope geometry and considering soil mechanics parameters, such as cohesion, inner shear angle, and material specific gravity. Simulations were conducted under two main conditions, namely dry conditions and conditions saturated with pore water pressure and seismic loads. The analysis showed that under dry conditions, the factor of safety (FS) of the slope was 2.45, indicating a stable condition. However, under saturated conditions with a pore water pressure of 0.2 and a seismic load of 0.2, the FS decreased to 1.1, indicating a critical condition. This study confirms that pore water pressure and seismic loads have a significant effect on slope stability. Therefore, mitigation in the form of drainage management and optimal slope geometry design is necessary to reduce the risk of landslides.